Evidence-based non-residential waste analysis to support 3R strategies and food recovery hierarchy: a case study in Solok Selatan - Fauzi, Mhd.; Aziz, Rizki; Chyntia, Nanda; Titani, Fena Retyo; Afrianto, Andika Wahyu (Universitas Muhammadiyah Surakarta, 2026)
The amount of waste generation that increases without being accompanied by good waste management will cause pollution and decrease the aesthetic value of the environment. Non-residential waste originating from non-residential activities is also one of the contributors to waste entering the landfill. This study aims to analyze non-residential waste generation and composition as an evidence-based reference for each source in implementing the 3R concept and the Food Recovery Hierarchy (FRH). The number of sampling sets was determined at a minimum of 10% of each type of facility following SNI 19-3964-1994. Sampling was carried out on eight consecutive days with 14 sampling points in Area 1, 14 in Area 2, and 11 in Area 3. The total non-residential waste generation was 46.79 m³/day (9.49 tons/day). Organic waste dominated the composition, accounting for 35–37% as food waste, followed by plastic (24–29%) and paper (14–20%). The high proportion of biodegradable and recyclable materials indicates significant potential for composting, recycling, and food recovery strategies at the source level. Implementing source-level 3R and FRH approaches could substantially reduce landfill dependency and extend landfill lifespan. This study addresses a knowledge gap by linking source-level non-residential waste characterization with the practical implementation of the 3R concept and the Food Recovery Hierarchy. This study provides quantitative evidence to guide localized waste minimization strategies in non-residential sectors.